Isolated Perihepatic Peritoneal Leiomyoma: A Case Report - Seul Ki Kim; Tae Young Lee (Journal of the Korean Society of Radiology)
Peritoneal leiomyomas are extremely rare. Most reported cases are that of disseminated peritoneal leiomyomatosis, making isolated leiomyoma an uncommon occurrence. Given that isolated leiomyoma is rare, the preoperative diagnosis of isolated leiomyoma is challenging. To date, very few reports have described the radiological findings of isolated peritoneal leiomyoma. This study aimed to present a rare case of isolated peritoneal leiomyoma in the perihepatic region of a 54-year-old female, and present the US, CT, and MRI based radiological findings of the case.